PENGARUH CAPITAL INTENSITY, SALES GROWTH, INVENTORY INTENSITY DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Anggun Puspita Sari; Iren Meita (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
This study aims to analyze the effect of Capital Intensity, Sales Growth, Inventory Intensity, and Firm Size on Tax Avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. Tax avoidance refers to a legal strategy used by companies to minimize tax liabilities without violating tax regulations. This research employs a quantitative approach using multiple linear regression analysis. The sample was determined using purposive sampling, resulting in 68 observations from 17 companies over four years. The results show that Capital Intensity, Sales Growth, and Inventory Intensity significantly affect Tax Avoidance, while Firm Size does not have a significant effect. Capital Intensity and Sales Growth have a negative effect, while Inventory Intensity has a positive effect on Tax Avoidance. These findings suggest that internal company characteristics, especially asset structure and sales growth, play a crucial role in determining the level of tax avoidance carried out by a company. This study is expected to serve as a reference for academics, practitioners, and tax authorities in understanding the determinants of tax avoidance practices in the food and beverage industry sector.